Exploring dual inhibitory role of febrifugine analogues against Plasmodium utilizing structure-based virtual screening and molecular dynamic simulation - Pandey, Rajan Kumar; Narula, Aruna; Naskar, Manisha; Srivastava, Shubham; Verma, Parmila; Malik, Ruchi; Shah, Priyanka; Prajapati, Vijay Kumar (Journal of biomolecular structure & dynamics, 2017)
Malaria is an endemic disease caused by the protozoan parasite Plasomodium falciparum. Febrifugine analogues are natural compound obtained from the traditional Chinese herbs have shown significant antimalarial and anticancerous efficacy in experimental model. Development of resistance against the existing antimalarial drug has alarmed the scientific innovators to find a potential antimalarial molecule which can be further used by endemic countries for the elimination of this disease. In this study, structure-based virtual screening and molecular dynamics (MD) base approaches were used to generate potential antimalarial compound against plasmepsin II and prolyl-tRNA synthetase of Plasmodium. Here, we have docked series of febrifugine analogues (n = 11,395) against plasmepsin II in three different docking modes and then it was compared with previously reported target prolyl-tRNA synthetase. Extra precision docking resulted into 235 ligands having better docking score were subject for QikProp analysis. Better ligands (n = 39) obtained from QikProp analysis were subject for ADMET prediction and docking protocol validation through the estimation of receiver operator characteristics. In the later stage, 24 ligands obtained from ADMET study were subject for the estimation of binding energy through MM-GBSA and same were also docked against prolyl-tRNA synthetase to get compounds with dual inhibitor role. Finally, MD simulation and 2D fingerprint MACCS study of two best ligands have shown significant interaction with plasmepsin II and homology against known active ligand with noteworthy MACCS index, respectively. This study concludes that FA12 could be potential drug candidate to fight against Plasmodium falciparum parasites.